2011
DOI: 10.1104/pp.111.174268
|View full text |Cite
|
Sign up to set email alerts
|

Tomato RAV Transcription Factor Is a Pivotal Modulator Involved in the AP2/EREBP-Mediated Defense Pathway    

Abstract: Ralstonia solanacearum is the causal agent of bacterial wilt (BW), one of the most important bacterial diseases worldwide. We used cDNA microarray to survey the gene expression profile in transgenic tomato (Solanum lycopersicum) overexpressing Arabidopsis (Arabidopsis thaliana) CBF1 (AtCBF1), which confers tolerance to BW. The disease-resistant phenotype is correlated with constitutive expression of the Related-to-ABI3/VP1 (RAV) transcription factor, ethylene-responsive factor (ERF) family genes, and several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 55 publications
(90 reference statements)
2
113
0
4
Order By: Relevance
“…ERF5 was also demonstrated to positively regulate SA signaling and plant immunities against the bacterial pathogen Pst DC3000 and improve plant resistance to pathogens by activating several PR genes (Moffat et al, 2012;Son et al, 2012). In tomato, the overexpression of ERF5 was observed to induce PR genes and conferred tolerance to Ralstonia solanacearum (Li et al, 2011). This study suggested an alternative approach to enhance plant resistance through ERF5, which can be regulated by a low concentration of peptide without the use of transgenes.…”
Section: Discussionmentioning
confidence: 97%
“…ERF5 was also demonstrated to positively regulate SA signaling and plant immunities against the bacterial pathogen Pst DC3000 and improve plant resistance to pathogens by activating several PR genes (Moffat et al, 2012;Son et al, 2012). In tomato, the overexpression of ERF5 was observed to induce PR genes and conferred tolerance to Ralstonia solanacearum (Li et al, 2011). This study suggested an alternative approach to enhance plant resistance through ERF5, which can be regulated by a low concentration of peptide without the use of transgenes.…”
Section: Discussionmentioning
confidence: 97%
“…ERF subfamily TFs can bind to the GCC box (AGCCGCC) in the promoters of ethyleneinducible genes that encode pathogenesis-related proteins (Ohmetakagi and Shinshi 1995;Wan et al 2014;Deokar et al 2015). RAV subfamily TFs are involved in many physiological and developmental pathways (Woo et al 2010;Leivar and Quail 2011), and biotic and abiotic stresses (Sohn et al 2006;Li et al 2011). The AP2/ ERF TF-like protein At4g13040 (Soloist) in Arabidopsis positively regulates the accumulation of salicylic acid and the defense against bacterial pathogens (Giri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that genes relative to both ethylene and salicylic acid defence signal transduction pathways were up-regulated in tomato plants infected by R. solanacearum (Milling et al 2011). In addition, transgenic tomatoes overexpressing ethylene-responsive transcription factor 5 gene (SlERF5) displayed better tolerance to bacterial wilt (Li et al 2011). Resistance to R. solanacearum in the tomato might be achieved, at least in part, by triggering the salicylic acid-defence-signalling pathway (Pan et al 2010).…”
Section: Discussionmentioning
confidence: 99%